Multi-Interacting Natural and Anthropogenic Stressors on Freshwater Ecosystems: Their Current Status and Future Prospects for 21st Century - Banaduc, Doru (2024)
The inheritance of historic human-induced disruption and the fierceness of its impact change aquatic ecosystems. This work reviews some of the main stressors on freshwater ecosystems, focusing on their effects, threats, risks, protection, conservation, and management elements. An overview is provided on the water protection linked to freshwater stressors: solar ultraviolet radiation, thermal pollution, nanoparticles, radioactive pollution, salinization, nutrients, sedimentation, drought, extreme floods, fragmentation, pesticides, war and terrorism, algal blooms, invasive aquatic plants, riparian vegetation, and invasive aquatic fish. Altogether, these stressors build an exceptionally composite background of stressors that are continuously changing freshwater ecosystems and diminishing or even destroying their capability to create and maintain ongoing natural healthy products and essential services to humans. Environmental and human civilization sustainability cannot exist without the proper management of freshwater ecosystems all over the planet; this specific management is impossible if the widespread studied stressors are not deeply understood structurally and functionally. Without considering each of these stressors and their synergisms, the Earth’s freshwater is doomed in terms of both quantitative and qualitative aspects.